FUTURE GENERATIONS OF WIRELESS NETWORKS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Wireless communication technologies have transformed modern society by enabling seamless connectivity across the globe. From the first generation (1G) to the current deployment of fifth-generation (5G) networks, wireless technologies have continuously evolved to meet increasing demands for higher speed, lower latency, and greater reliability. This paper explores the future generations of wireless networks, focusing on 6G and beyond. Using a qualitative literature review, the study examines emerging technologies, expected applications, challenges, and future opportunities. The findings indicate that artificial intelligence, terahertz communication, intelligent surfaces, and quantum technologies will significantly shape the next generation of wireless communication systems.
Keywords: Wireless Networks, 6G, Artificial Intelligence, Terahertz Communication, Internet of Things, Future Communication.